Constraints Faced by the Farmers in the Production and Marketing of Onions in the Western Undulating Zone of Odisha, India - , Sattaswarup Rout; , R. K. Rout; , S.K Sahoo; , B. K. Mandal; , L.K. Das; , B.P. Gantayat; , Simly Das; , R. L. Moharana; , C. Behera; , L. Jena; , T. Badjena; , T. Pattnaik; et al. (Archives of Current Research International, 2024)
This paper aimed to investigate the limitations associated with onion farming in the western undulating agroclimatic zone of Odisha, specifically regarding production, marketing, and storage. The study employed a multi-stage purposive sampling technique. The state was divided into 10 zones based on agro-climatic characteristics, and the district from the western undulating zone, Kalahandi districts, was purposively chosen since many farmers in these regions, like others in Odisha, cultivate onions throughout the winter season. A total of 90 farmers (45 from Bhawanipatna block and 45 from Golamunda block) were selected at random and interviewed directly for the purpose of study. Furthermore, the location, climatic conditions, and soil are ideal for onion cultivation. Kalahandi was chosen in 2021–2022. According to the survey, labour shortages for weeding, ignorance of improved varieties, high labour costs, ineffective and expensive weedicides, high seed costs, etc. were the top five problems faced by onion growers. The main difficulties faced by onion growers during marketing included low prices during harvest, which were followed by sharp price fluctuations, high transportation costs, payment delays, a lack of market news and information, a lack of storage facilities, etc. in the research area. To ensure an effective produce marketing system, the government, developmental agencies, marketing boards, and NAFED should intervene by enhancing the market infrastructure at the taluk and district levels and supplying timely market information. Farmers may be able to overcome the issue of price fluctuations if government authorities intervene promptly and announce an extension or announcement of the government support price for onion crops.